Professional development of EFL teachers in Uzbekistan: from traditional methods to global competency standards - Karimbaeva, Asal (The Lingua Spectrum, 2025)
The development of English as a Foreign Language (EFL) teachers in Uzbekistan is experiencing a significant transformation. This article discusses the shift from traditional, teacher-centered training methods toward modern, global competency standards that emphasize communicative skills, digital literacy, and intercultural competence. International cooperation and technological advances have played a critical role in this evolution. Despite challenges such as unequal access and resistance to change, ongoing reforms suggest promising progress in improving English language education in Uzbekistan. The article highlights the need for continuous support and adaptation to local contexts to achieve sustainable development in teacher training.